Investigating the relationship between superstition and sports success in Iraqi football league players - Reza Aminzadeh; Bahador Azizi; Ahmad Mahmoudi (Sport Sciences and Health Research)
Background: Superstitions and rituals have long been a part of sports culture, with many athletes believing that they can bring good luck or improve their performance.Aim: The aim of this study was to investigate the relationship between superstitions and sports success in Iraqi football league players.Materials and Methods: This study used a descriptive-correlational analysis method, with data collected in the field from a sample of 200 players randomly selected from the population of players in the Iraqi football premier league. Two standard questionnaires, Superstition in Sports and Sports Success Questionnaire, were used to collect data, both of which were designed based on the Likert five value range.Results: The study found that there is a significant relationship between superstitions and sports success, with the most important priority related to the component of "team ritual" (5.58) in superstitions and "commitment" (4.58) in sports success. The study also found that 37% of changes in sporting success are related to superstitious components.Conclusion: Based on the study's findings, it can be concluded that the use of superstitious rituals can have a positive effect on the sports success of athletes.